Effect of screw spacing on behavior of axially loaded back-to-back cold-formed steel built-up channel sections - Ting, Tina Chui Huon; Roy, Krishanu; Lau, Hieng Ho; Lim, James BP (Advances in structural engineering, 2018)
In cold-formed steel structures, such as trusses, wall frames, and portal frames, the use of back-to-back built-up cold-formed steel channel sections for the column members is becoming increasingly popular. In such an arrangement, intermediate fasteners at discrete points along the length prevent the individual channel sections from buckling independently. Current guidance by the American Iron and Steel Institute and the Australian and New Zealand Standards for built-up sections describes a modified slenderness approach, to take into account the spacing of the screws. Limited experimental tests or finite element analyses, however, have been reported in the literature for such sections to understand the effect of screw spacing. This issue is addressed herein. The results of 30 experimental tests are reported, conducted on back-to-back built-up cold-formed steel channel sections covering stub columns to slender columns. A finite element model is then described which shows good agreement with the experimental test results. The finite element model is then used for the purposes of a parametric study comprising 144 models. It is shown that while the modified slenderness approach is in general conservative, for stub columns it can be unconservative by around 10%.